2007
DOI: 10.1128/jb.00706-07
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Visualization of a Fibrillar Array in the Cell Wall of Filamentous Cyanobacteria and Its Implications for Gliding Motility

Abstract: Many filamentous cyanobacteria are motile by gliding, which requires attachment to a surface. There are two main theories to explain the mechanism of gliding. According to the first, the filament is pushed forward by small waves that pass along the cell surface. In the second, gliding is powered by the extrusion of slime through pores surrounding each cell septum. We have previously shown that the cell walls of several motile cyanobacteria possess an array of parallel fibrils between the peptidoglycan and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…A second theory postulates that contraction waves driven by contractile fibers provide the motive force. Evidence in support of this theory is limited to a handful of conflicting ultrastructure studies that found various fibrils either internal or external to the outer membrane in several strains of filamentous cyanobacteria (Halfen and Castenholz, 1970;Hoiczyk and Baumeister, 1995;Adams et al, 1998;Read et al, 2007). The third theory holds that like Synechocystis, T4P provide the motive force.…”
Section: Introductionmentioning
confidence: 99%
“…A second theory postulates that contraction waves driven by contractile fibers provide the motive force. Evidence in support of this theory is limited to a handful of conflicting ultrastructure studies that found various fibrils either internal or external to the outer membrane in several strains of filamentous cyanobacteria (Halfen and Castenholz, 1970;Hoiczyk and Baumeister, 1995;Adams et al, 1998;Read et al, 2007). The third theory holds that like Synechocystis, T4P provide the motive force.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of this phenomenon is difficult to explain due to many unresolved questions regarding Cyanobacteria movements and sheath formation (Adams et al, 1999;Hoiczyk, 2000;Wolgemuth & Oster, 2004;Read et al, 2007). The most helpful seem to be the findings of Hoiczyk and Baumeister, who described two factors most likely responsible for gliding motility in Phormidium (Hoiczyk & Baumeister, 1997.…”
Section: Discussionmentioning
confidence: 99%
“…We already mentioned gliding motility (also a hot topic). In gliding cyanobacteria, there are filamentous helical structures in the S-layer, adjacent to the muccelage pore channels, which are evidently involved in the rolling-translating motion (Read, Connell, Adams, 2007) [75] (Adams, 2001) [1].…”
Section: "Egg-beater" Model For Myxobacteria Gliding: a Clue For Synementioning
confidence: 99%